The sources of competitive advantage from the perspective of project management – results of empirical studies - Dolata Magdalena (Management)
The aim of the paper is entering the discussion concerning the sources of competitive advantage in project management in basic local government units in Poland. The focus of the paper is placed on the selected elements of the sources of competitive advantage in basic local government units in Poland, namely tasks implemented in projects. The paper consists of two main parts. In the first part of the paper, a starting point was the presentation of the essence of competitiveness and competitive advantage in the process of project management from the perspective of local government units in Poland. In the second one, the results of the research proceedings concerning the importance of tasks implemented in projects in projects in basic local government units in Poland were discussed. The considerations presented in the paper refer to the results of the research proceedings, which took place in two stages. The first stage of the studies was conducted in 2013 and it concerned the years 2010-2012, the second stage – in 2018, and it concerned the years 2016-2018.